Figurative Language in Ariana Grande Song Lyrics - Simatupang, Echa F E; Jayantini, I Gusti Agung Sri Rwa; Resen, I Wayan (Journal of Language and Applied Linguistics, 2023)
The study aims to find out and analyze the meaning of every type of figurative language in the song lyrics. Figurative language is a language style used by the writer or speaker to convey a message imaginatively and in a mode which aims to make the reader get effect from language style. The data in this research were analyzed using qualitative descriptive methods and based on the linguistic theory that is used in semantics. This study proposes two of problem those are, first what types of figurative language and second what is the meaning of the figurative language used in Ariana Grande’s song lyrics. To get the meaning of those figurative languages, several expert theories were used for this research on the classification and definition of figurative language. There are two theories that were used in conducting this research. This first theory of types of figurative language is proposed by the expert, Knickerbocker and Reninger and the second theory of figurative language and the types of meaning theories by Leech.